β-Catenin mediated TAM phenotype promotes pancreatic cancer metastasis via the OSM/STAT3/LOXL2 axis - Yijia Zhang; Xinya Zhu; Liyuan Chen; Tianyu Gao; Guang Chen; Jin Zhu; Guoyu Wang; Daiying Zuo (Neoplasia: An International Journal for Oncology Research)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by its aggressive nature and dismal prognosis, largely attributed to its unique tumor microenvironment. However, the molecular mechanisms by which tumor-associated macrophages (TAMs) promote PDAC progression, particularly the role of β-catenin signaling in regulating TAM phenotype and function, remain incompletely understood.Initially, we performed comprehensive analyses of RNA-seq and single-cell RNA-seq (scRNA-seq) datasets to investigate OSM and LOXL2 expression patterns in PDAC. Subsequently, the regulatory relationship between β-catenin and OSM in TAMs was examined using THP-1-derived macrophages. Furthermore, the functional impact of TAM-derived OSM on PDAC progression was evaluated through in vitro co-culture systems and an in vivo Panc02 lung metastasis model. Additionally, mechanistic studies employed pharmacological inhibitors and genetic approaches targeting β-catenin, OSM, and STAT3 signaling.Notably, elevated expression of OSM and LOXL2 in PDAC specimens significantly correlated with poor patient survival. Intriguingly, scRNA-seq analysis revealed that β-catenin signaling was uniquely activated in TAMs among immune cells, which consequently regulated both TAM polarization and OSM expression. These OSM-expressing TAMs exhibited a distinct hybrid M1/M2 phenotype. Besides, our transcriptional profiling of TAMs revealed concurrent activation of both pro- and anti-inflammatory programs, with enrichment in Wnt signaling pathways. RNA-seq analysis of PDAC cells exposed to TAM-derived factors demonstrated enhanced mesenchymal transition and stemness properties, with direct enrichment of OSM signaling and extracellular matrix remodeling pathways. Mechanistically, β-catenin activation directly regulated both TAM phenotype and OSM expression, while TAM-conditioned medium enhanced PDAC cell migration, invasion, and lung metastasis. Importantly, inhibition of β-catenin signaling simultaneously altered TAM polarization and reduced OSM expression, which substantially attenuated epithelial-mesenchymal transition (EMT) in co-cultured PDAC cells. Moreover, STAT3 inhibition abolished OSM-induced LOXL2 expression and subsequent EMT programming.Collectively, we identified a novel β-catenin/OSM-STAT3/LOXL2 signaling axis mediating TAM-induced PDAC progression. This pathway not only elucidates a previously unrecognized mechanism of β-catenin-mediated regulation of TAM function and phenotype but also presents potential therapeutic targets for intervention.